Design And Development Of Remotely Pumped Erbium Doped Fiber Amplifier Transmission System - Zainal Abidin, Mohd Shahnan (2004)

(untitled)
Erbium Doped Fiber Amplifier (EDFA) has been deployed extensively in optical communication systems especially for a long haul transmission link. Basically, EDFA requires a local pump laser for its optical amplification. This design will encounter problem if the amplifier is located at the middle of transmission line where power supply for the pump laser is unavailable. Therefore, remotely pumped amplifier can overcome the problem by injecting the pump light from either side of the transmission ends; transmitter or receiver. This dissertation reveals a new technique of designing a repeaterless transmission system using a remotely pumped EDFA. By varying the length of transmission fiber before and after EDFA, its location can be optimized for a specific pump power. A bit error rate is used as the main performance parameter and its threshold value is set at better than 10-10. The optimized location of EDFA will lead to the maximum transmission distance where it is found that the location of EDFA is closer to the receiver side.In conclusion, the EDFA location on transmission line using remotely pumped technique gives major impact to the system’s performance.